PERANAN PENDIDIKAN DALAM MENGHINDARI PERGAULAN BEBAS ANAK USIA REMAJA - Nadirah, Sitti (Pusat Studi Gender dan Anak, IAIN Palu, 2017)
The promiscuity of juvenile delinquency is increasingly showing a very alarming increase. This paper examines the role of education in avoiding the promiscuity of adolescent children. With education it will create the formation of character. With the character of teenage children will